How the west controls pharmaceutical prices: lessons for Malaysia - Amirul Ashraf; Ong, Siew Chin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Drug price in Malaysia has increased substantially over the years. Malaysian policymakers may learn from the Western countries on how to control pharmaceutical spending. We conducted a review to assess the pharmaceutical strategies adopted in Western countries to curb pharmaceutical pricing and compared it with thecurrent Malaysian system. The study found that the European countries adopted a regulated pharmaceutical market. In this regulated market, the price of the drugs will be determined using external reference pricing. The reimbursement and pricing of the drugs are also based on a set of guidelines rather than arbitrary nature. Additionally, the health technology assessment in the European countries utilised rating systems to categorise the added therapeutic benefit of the drugs. This rating system will add more information for price negotiation between the government and pharmaceutical manufacturers. Furthermore, cost-effectiveness analysis is also being incorporated into the decision-making process to ascertain the optimal use of scarce health resources. On top of that, pooled procurement system has been established in order to benefit from the higher volume purchasing. These measures may help Malaysia to ensure that the pharmaceutical spending remain sustainable and that Malaysians, will continue to have access toward a high-quality and affordable healthcare in the future.